Magnetohydrodynamic Nanofluid Flows Over a Smart Fabric Under the Effects of Mixed Convection, Magnetic Field, Stretching Force, and Radiation - Zaitun; Widodo B; Imron C; Adzkiya D (Outline Publisher, 2025)
The study of Magnetohydrodynamic (MHD) has been widely discussed with complex problems. Just as this topic involves inductive polymers or smart fabrics for engineering in machinery or protective equipment. The smart fabrics that can be involved in MHD studies become a useful material. The smart fabric is a sheet of inductive polymer that can be an influence in the MHD analysis as well as a parameter that can be considered. In this study, the MHD of nanofluid, namely Iron-(III)-oxide flows past in smart fabrics under influence of magnetic field and radiative flux is studied by constructing a mathematical model and then the model solved numerically using the Keller-Box scheme. The effect of Mixed Convection and stretching parameter is considered on the model. Numerical simulations were carried out to examine the effect of the parameters, are obtained the profile of velocity and temperature increase when the magnetic and stretching parameters increases, the velocity profile and temperature decreases when the Prandtl number are increases, the profiles of velocity are decreases and temperature increases when porosity variable and volume fraction parameter’s value increases, and the profile of temperature increase when the mixed convection’s value and the radiation parameter increases.